Small states and regional stability in South Asia - Kabir, Humayun; Bangladesh Institute of International and Strategic Studies (Dhaka : The University Press, 2005)
Contributed articles on political conditions in South Asia presented and discussed in many workshops and seminars.
Small states in global perspective : in search of a role model in regional stability / Shaheen Afroze -- Nuclearisation and regional security in South Asia : small states' perspective / Mainuddin Ahmed -- Globalisation and economic security : the perspectives of small states in South Asia / Mirza Azizul Islam -- The impact of the war on terrorism on 'small states' : the South Asian context with special reference to Bangladesh / Imtiaz Ahmed -- Common risks and common solutions for the smaller states of South Asia : a comparative perspective / Abul Kalam Azad -- Democracy and conflict management in South Asia / Ataur Rahman.
"Bangladesh Institute of International and Strategic Studies."
Includes bibliographical references and index.
Keywords: States, Small -- Congresses; South Asia -- Politics and government -- Congresses